‘Languages are not enemies but friends’: Primary school teachers’ attitudes towards the use of translanguaging in the EFL classroom - Gayete, Gema (Neofilolog, 2025)
This investigation is conducted in the primary school context of the Valencian Community (Spain), which is characterised by the presence of three teaching languages: (i) Catalan, as the minority language, (ii) Spanish, as the majority language, and (iii) English, as the main additional language. Regardless of this multilingual curriculum, the L3 (English) of students is taught in isolation without considering their L1s. Therefore, this study aimed at analysing 12 EFL primary school teachers’ attitudes towards the use of translanguaging practices in the EFL classroom. Moreover, we explored the effect of individual variables on teachers’ attitudes, which include teachers’ L1(s) and previous training on multilingualism. Practitioners responded to a written questionnaire and took part in face-to-face semi-structured interviews. Data were codified and examined using SPSS and NVivo softwares. Findings show that teachers recognised the benefits of translanguaging pedagogies for scaffolding target language learning in the early EFL classroom. Although attitudinal differences were noticed among teachers with different L1s, they were not statistically significant. Hence, our results suggest that these primary school teachers are open to the introduction of more multilingual approaches towards L3 teaching and learning that consider young learners’ language backgrounds and previous experience as language learners.